Development Of Cryopreservation In Denrobium Bobby Messina Using PVS2 Vitrification And Encapsulation-Dehydration Methods - Anthony, Jessica Jeyanthi James (2012)
Two new cryopreservation techniques, PVS2 vitrification and encapsulationdehydration, were applied on PLBs of Dendrobium Bobby Messina, highly-prized orchid in Malaysia, with survival monitored through observations of growth and the 2,3,5-triphenyltetrazolium chloride (TTC) assay. In the vitrification method, the parameters optimized were PLBs size, preculture concentration, preculture durations and PVS2 incubation temperature and duration. In the encapsulation-dehydration method, the parameters optimized were PLBs size, preculture concentration, preculture duration and dehydration period with silica gel. In cryopreservation of Dendrobium Bobby Messina by vitrification technique, the optimized protocol based on TTC spectrophotometrical analysis and growth recovery were 3-4mm PLBs precultured in 0.2M sucrose for 1 day, treated with a mixture of 2M glycerol and 0.4M sucrose supplemented with half strength liquid MS media at 25°C for 20 minutes and subsequently dehydrated with plant vitrification solution 2 (PVS2) at 0°C for 20 minutes prior to storage in liquid nitrogen. Following rapid warming in a water bath at 40°C for 90 seconds, the PLBs were washed with half strength liquid MS media supplemented with 1.2M sucrose. Subsequently, the PLBs were cultured on half strength semi-solid MS media supplemented with 2% (w/v) sucrose without any growth regulators. The optimized vitrification method was successful in preserving this orchid as it produced growth recovery in non-cryopreservaed and cryopreserved PLBs up to 100% and 40% for Dendrobium Bobby Messina